1996
DOI: 10.1046/j.1365-2249.1996.d01-824.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor antagonist in saliva; characterization in normal saliva and reduced concentration in Sjo¨gren's syndrome (SS)

Abstract: SUMMARYThe characterization of a salivary factor cross-reacting with IL-1 receptor antagonist (IL-1Ra) is described. The apparent molecular weights of two species were 23 kD, consistent with the secreted peptide (sIL-1Ra), and 20 kD, consistent with the intracellular peptide (icIL-1Ra). It had an inhibitory activity on IL-1-stimulated fibroblasts, which is characteristic of IL-1Ra. Its source was the oral mucosa and not the salivary glands. Saliva from patients with SS contained significantly less IL-1Ra than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…IL-1RA is an anti-inflammatory cytokine that competes with IL-1α and IL-1β for binding to the IL-1 receptor (40). IL-1RA has been found to be present in saliva in significantly higher amounts than in peripheral blood and is generally secreted by oral keratinocytes in biologically active form (41). Linkov et al carried out a comprehensive serum-based biomarker evaluation, where they found IL-1RA levels to be significantly raised in head and neck squamous cell carcinoma (42).…”
Section: Cancer Investigationmentioning
confidence: 99%
“…IL-1RA is an anti-inflammatory cytokine that competes with IL-1α and IL-1β for binding to the IL-1 receptor (40). IL-1RA has been found to be present in saliva in significantly higher amounts than in peripheral blood and is generally secreted by oral keratinocytes in biologically active form (41). Linkov et al carried out a comprehensive serum-based biomarker evaluation, where they found IL-1RA levels to be significantly raised in head and neck squamous cell carcinoma (42).…”
Section: Cancer Investigationmentioning
confidence: 99%
“…B lymphocytes make up ϳ20% of the infiltrating cell population and monocytes/macrophages are also present (50). Infiltrating lymphocytes produce proinflammatory cytokines that have been shown to play a role in the pathogenesis of SS (10,21,35,71,73). During the evolution of the inflammatory response in SS, an array of adhesive interactions occurs between immune cells and target tissues (2,22,75,89).…”
Section: Primed Cd4mentioning
confidence: 99%
“…In contrast, the inflammatory site is more likely unbalanced in favor of IL-1, especially in severe lesions [27] and insufficient production of endogenous IL-1ra may contribute to the pathogeny of these conditions [see [22] for more details].…”
Section: Il-1 Family: Generalitiesmentioning
confidence: 99%